Oral Health-Related Quality of Life after Fixed Partial Denture among Patients Visiting a Tertiary Care Hospital - Alam, Munna; Adhikari, Galav; Chadhary, Samin; Maharjan, Anjana (Annapurna Journal of Health Sciences, 2024)
Introduction: Fixed Partial Dentures (FPDs) are the most common choice for dental rehabilitation after tooth loss. These dentures can impact oral health and quality of life among patients. This study thus aims to know the oral health-related quality of life with the help of the Oral Health-related Impact Profile -14 questionnaire among the patients with FPDs in Kathmandu. Methods: A descriptive cross-sectional study was carried out among 250 patients with FPDs in the Department of Dental Surgery, Trichandra Military Hospital. The participants were selected by convenient sampling after obtaining informed consent between April 2023 to September 2023 among the individuals with tooth-supported fixed partial dentures. The oral health-related quality of life was assessed with the help of the Oral Health-related. Impact Profile questionnaire which consists of 14 question items and is the standard tool used globally for assessing the oral healthrelated quality of life SPSS-16 version was used to know the distribution of various responses in each of these question items. Results: Among 250 cases of fixed partial dentures, the maximum number of participants experiencing adverse impacts had painful aching in the mouth (11.6%), feeling self-conscious (10%), and uncomfortable eating any foods (8.8%). The distribution of severity of the adverse impacts was mostly in the none category (51.6%), little (23.6%), moderate (7.2%) and great (1.6%). Conclusion: The distribution of severity of the adverse impact of tooth-supported Fixed partial dentures on oral health-related quality was none to little as per the oral health impact profile questionnaire-14. This is supportive of the success of fixed partial dentures in the study population.